PROFIL PEMECAHAN MASALAH MATEMATIKA SISWA SMP DENGAN KECERDASAN INTERPERSONAL DITINJAU BERDASARKAN GENDER - Agung Wicaksono (Koordinat Jurnal MIPA, 2020)
This study is a qualitative research that aims to get a description of the profile of students mathematical problem solving grade IX SMP with interpersonal intelligence based on gender differences on Polya phase. The subjects of this study were students at grade IX of Junior High School who had a interpersonal intelligence based on gender differences. This study was conducted at the Junior High School in Palu, Central Sulawesi. Based on data analysis can be concluded that male students who have interpersonal intelligence can do all stages problem solving of mathematics, that is understand the problem, make a plan, carry out our plan, and look back at the completed solution with tendencies to build up interaction with other people to easily understand the problems. While female students who have interpersonal intelligence while do some stage problem solving of mathematics need help too much, that is understand the problem and make a plan. As for the stages carry out our plan, and look back at the completed solution the female students do with full of confidences.